Bioactivity of some compounds isolated from the heartwood of Dalbergia oliveri Gamble ex Prain - Loan, Pham Thanh; Thai, Tran Huy; Kiem, Phan Van; Tuan Anh, Hoang Le; Minh, Chau Van; Thao, Do Thi; Suu, Tran Thi (Academia Journal of Biology, 2013)
Several species of the genus Dalbergia have been used for a long time in Vietnam as traditional medicine, there was a few papers concerning biology and taxonomy of Dalbergia in Vietnam. In our study, first time ten bioactive compounds isolated from the heartwood of Dalbergia oliveri were evaluated. The results showed that from the cytotoxic assay, two compounds numbered as (9) (6aR,11aR)-3,8-dihydroxy-9-methoxypterocarpan and numbered as (10) 3hydroxy-9 methoxyterocarpan exhibited strong cytotoxic activities with the IC50 values ranging from 3.76 mg/ml to 7.09 mg/ml. The compound numbered as (9) (6aR,11aR)-3,8-dihydroxy-9-methoxypterocarpan also showed a mild antioxidative activity with the ED50 were 31.46 mg/ml. None of the ten tested compounds were evaluated for the anti-microbiological activity in vitro.